2016
DOI: 10.1080/1369183x.2015.1113742
|View full text |Cite
|
Sign up to set email alerts
|

Modes of incorporation: a conceptual and empirical critique

Abstract: Entering the debate over segmented assimilation, this paper seeks to refocus discussion on a core, but neglected claim: that inter-group disparities among immigrant offspring derive from differences in a contextual feature shared by immigrant and immigrant descendants: a nationality's mode of incorporation. The paper engages in both theoretical and empirical assessment. We critically examine the concept of mode of incorporation, demonstrating that its operational implications have not been correctly understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Comparing names generates coefficients that are only inconsistently significant (Waldinger and Catron 2016). An index ranking nationalities according to the advantage/disadvantage associated with a mode of incorporation produces more robust effects, but it is neither a meaningful metric (what, exactly, is entailed in a one-step difference in modes of incorporation?)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing names generates coefficients that are only inconsistently significant (Waldinger and Catron 2016). An index ranking nationalities according to the advantage/disadvantage associated with a mode of incorporation produces more robust effects, but it is neither a meaningful metric (what, exactly, is entailed in a one-step difference in modes of incorporation?)…”
Section: Resultsmentioning
confidence: 99%
“…Recent systematic evaluations of this approach using the CILS data (Waldinger and Catron 2016) have found that when systematically applied to all meaningful comparisons, and varying one dimension at a time, results are often inconsistent with the predictions of the modes of incorporation model. In additional analyses, which are available as Supplemental Material, we implement a similar approach using the IIMMLA and IMSGNY data and come to conclusions similar to those reported by Waldinger and Catron.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking past the medians, it becomes clear that Chinese immigrants vary dramatically on many traits that are associated with incorporation such as national origin, U.S. tenure, and life course state. Although it is well-established that each of these characteristics facilitates post-migration attainment [2, 6–8], scholars have increasingly called for more exploration of within-immigrant group variation on attributes such as these to adjudicate disparate findings about incorporation [912]. Because contemporary Chinese immigrants are the largest and most internally-diverse portion of the Chinese origin population, they provide a unique and important opportunity to answer this call.…”
Section: Introductionmentioning
confidence: 99%
“…The role salient ethnic boundaries play in explaining group-specific integration outcomes is a highly contested issue in migration research (Portes and Rumbaut 2001;Waldinger and Catron 2016;Wimmer and Soehl 2014). There is certainly ample empirical evidence of experiences of ethnic prejudice and discrimination, particularly in survey data and audit studies (Pager 2007;Strabac and Listhaug 2008).…”
Section: Introductionmentioning
confidence: 99%